Penerapan Metode Waterfall dalam Rancang Bangun Aplikasi Penyewaan Alat Perkemahan pada Selamet Outdoor Tambun - Rachmatsyah, Agus Dendi; Nafisha, Nurul Laili; H, Feri Prasetyo (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Abstract Slamet Outdoor Adventure is one of the camping and outdoor equipment rental service providers in Tambak. In this discussion the author explains in the background that slamet outdoor adventure still uses a manual system, starting from processing customer data, goods, packages, recording rental transactions, recording returns transactions and recording reports on all transactions. Then we need a specially designed program using Visual Basic 6.0 for the interface and the database uses MySQL which aims to store the data. With computerized camping equipment rental at Slamet Outdoor Adventure Shop this will make it easier for all transactions, so the system will run faster and more accurately and better than the previous system. By turning on the cycle flow of the waterfall diagramKeyword-Rental, Returns, waterfall